Organización del turismo comunitario en la parroquia flores, cantón Riobamba - Priscila Carolina, Montufar Zavala (2021)
ABSTRACT This research is focused on the problem that exists in Flores, which is the deficient organization of community tourism, not using natural and cultural heritage and finally with the insufficient tourist service that has limited community tourism in Flores. The following investigation was carried out to find out the reason why the Flores is unaware of community tourism, despite the fact that they have natural and cultural attractions. It is recognized for its carnival called "Sisay Pacha" and they have festivals, rituals, astronomy, green baskets, among other activities to offer. Chapter I consists of the problematic situation, formulation of the problem, justifications, objectives, hypotheses. Chapter II shows the theoretical framework includes the background of the research, theoretical bases of the research, philosophical framework and state of the art. Chapter III refers to the methodology that is included in the types and design of research, unit of analysis, study population, sample size, sample selection, operationalization of variables, consistency matrix, research techniques and instruments, validity and reliability of the instruments and analysis and presentation of the information. Chapter IV focuses on the results and discussion includes the analysis, interpretation and discussion of results, hypothesis tests, general and specific hypotheses, presentation of results, conclusions and recommendations. Chapter V is the design of the Food and Beverage Production Management Process under the guidelines of the ISO 9001-2015 Standard of Flores. Keywords: Organization, community tourism, ISO 9001-2015 Standards, natural heritage and cultural heritage Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 0602773301